Clinical features and prognosis of pediatric idiopathic sudden sensorineural hearing loss: A bi-center retrospective study - Li, Yingqiang; Zhou, Xiaowei; Dou, Zhiyong; Deng, Dongzhou; Bing, Dan (Frontiers in Neurology, 2023)
Objective Limited research has focused on the clinical features of sudden sensorineural hearing loss (SSNHL) in pediatric patients. This study is aimed to investigate the relationship between clinical features and the baseline hearing severity and outcomes of SSNHL in the pediatric population. Method We conducted a bi-center retrospective observational study in 145 SSNHL patients aged no more than 18 years who were recruited between November 2013 and October 2022. Data extracted from medical records, audiograms, complete blood count (CBC) and coagulation tests have been assessed for the relationship with the severity (the thresholds of the initial hearing) and outcomes (recovery rate, hearing gain and the thresholds of the final hearing). Results A lower lymphocyte count (P = 0.004) and a higher platelet-to-lymphocyte ratio (PLR) (P = 0.041) were found in the patient group with profound initial hearing than in the less severe group. Vertigo (β = 13.932, 95%CI: 4.082–23.782, P = 0.007) and lymphocyte count (β = −6.686, 95%CI: −10.919 to −2.454, P = 0.003) showed significant associations with the threshold of the initial hearing. In the multivariate logistic model, the probability of recovery was higher for patients with ascending and flat audiograms compared to those with descending audiograms (ascending: OR 8.168, 95% CI 1.450–70.143, P = 0.029; flat: OR 3.966, 95% CI 1.341–12.651, P = 0.015). Patients with tinnitus had a 3.2-fold increase in the probability of recovery (OR 3.222, 95% CI 1.241–8.907, P = 0.019), while the baseline hearing threshold (OR 0.968, 95% CI 0.936–0.998, P = 0.047) and duration to the onset of therapy (OR 0.942, 95% CI 0.890–0.977, P = 0.010) were negatively associated with the odds of recovery. Conclusions The present study showed that accompanying tinnitus, the severity of initial hearing loss, the time elapse and the audiogram configuration might be related to the prognosis of pediatric SSNHL. Meanwhile, the presence of vertigo, lower lymphocytes and higher PLR were associated with worse severity.